Taxonomic Revision of the genus Mesomphalia Hope, 1839 (Insecta, Coleoptera, Chrysomelidae) - Simões, Marianna V. P.; Monné, Marcela L. (Zootaxa, 2014)
A revision of the genus Mesomphalia Hope, 1839, is presented based on a detailed morphological study of all species, except M. ampliata Boheman, 1850 and M. albofasciculata Boheman, 1856. The genus and species are redescribed. One species is transferred to Stolas Billberg, 1820, as S. scrobiculata (Boheman, 1850) comb. nov.; one species is transferred to Cyrtonota Chevrolat, 1836, as C. pyramidata (Boheman, 1850) comb. nov.; M. sexmaculata Boheman, 1850 syn. nov. is a junior subjective synonym of M. turrita (Illiger, 1801); one new species M. spaethi Simões & Monné, sp. nov. is described. Following this revision, Mesomphalia now contains fourteen species. A key to the species, photographs and distribution maps are provided.